Improving English Vocabulary for Elementary School Students using Total Physical Response (TPR) Method - Salsabila, Della Hegian (Prosiding University Research Colloquium, 2021)
The purpose of this study was to determine the increase in English Vocabulary of Elementary School Students Using the Total Physical Response (TPR) Method. In this study, researchers using a quantitative approach with a quasi-experimental design for doing a way to compare groups. There are three techniques in data collection includes: observation, pre-test and posttest. After collecting data, researchers analyze, describe and finally conclude. Data will be analyzed using statistical analysis as follows with calculate the mean score of the pre-test and post-test to find out whether there is a significant difference in control and experimental groups. From this statement, it can be concluded that the TPar method will affect student learning outcomes. Therefore, it is time for teachers, schools, and related parties to use the TPR method to improve the quality of learning.